Effectiveness of on-the-Job Learning for Enterprisesâ Innovativeness - Kusum, P.P. Ajith; Yinghua, Song (International Research Journal of Management, IT & Social Sciences, 2017)
The mode of on-the-job learning â one of the methods of acquiring competencies still remains one of the main modes of acquiring workplace competencies in conventional industries in developing countries. This paper explores the impact of aforesaid mode of competency acquisition for enterprise innovativeness of an industry of Sri Lanka.Â  A structured questionnaire was used to gather primary data related to modes of acquiring competencies...